Diaphragmatic hernia following oesophagectomy for oesophageal cancer – Are we too radical?. (March 2016) - Argenti, F.; Luhmann, A.; Dolan, R.; Wilson, M.; Podda, M.; Patil, P.; Shimi, S.; Alijani, A.
Abstract: Background: Diaphragmatic herniation (DH) of abdominal contents into the thorax after oesophageal resection is a recognised and serious complication of surgery. While differences in pressure between the abdominal and thoracic cavities are important, the size of the hiatal defect is something that can be influenced surgically. As with all oncological surgery, safe resection margins are essential without adversely affecting necessary anatomical structure and function. However very little has been published looking at the extent of the hiatal resection. We aim to present a case series of patients who developed DH herniation post operatively in order to raise discussion about the ideal extent of surgical resection required. Methods: We present a series of cases of two male and one female who had oesophagectomies for moderately and poorly differentiated adenocarcinomas of the lower oesophagus who developed post-operative DH. We then conducted a detailed literature review using Medline, Pubmed and Google Scholar to identify existing guidance to avoid this complication with particular emphasis on the extent of hiatal resection. Discussion: Extended incision and partial resection of the diaphragm are associated with an increased risk of postoperative DH formation. However, these more extensive excisions can ensure clear surgical margins. Post-operative herniation can be an early or late complication of surgery and despite the clear importance of hiatal resection only one paper has been published on this subject which recommends a more limited resection than was carried out in our cases. Conclusion: This case series investigated the recommended extent of hiatal dissection in oesophageal surgery. Currently there is no clear guidance available on this subject and further studies are needed to ascertain the optimum resection margin that results in the best balance of oncological parameters vs. post operative morbidity. Highlights: Shows the potential for intra-thoracic herniation following oesophageal resection. Raise debate about the extent of resection needed for oncological safe margins while reducing postoperative complications. Shows the potential for severe morbidity and mortality after such an extensive resection.